Preparation and Reactivity Studies of Four and Five coordinated Amidinate Aluminum Compounds - Banerjee S.; Kumar C.A.; Bose S.; Sarkar S.K.; Gupta S.K.; Graw N.; Köhler C.; Herbst-Irmer R.; Stalke D.; Dutta S.; Koley D.; Roesky H.W. (My University, 2025)
Synthesis of four and five coordinated aluminum amidinate (PhC(NtBu)2=L) compounds are reported herein along with their single-crystal X-ray structures and detailed characterizations using both, experimental and computational techniques. LAlCl2 (1) and L2AlCl (2) were synthesized by treating AlCl3 with PhC(NtBu)2Li in an equivalent ratio of 1 : 1 and 1 : 2, respectively. [LAl(C2H5)Cl] (3) was prepared from a reaction of AlCl2(C2H5) with PhC(NtBu)2Li in an equivalent ratio of 1 : 1. Reactivity of 3, an amidinate based organo-aluminum compound is explored for the various reactions. 3 produced [LAl(C2H5)(μ-F)]2 (4) on treatment with Me3SnF. Interestingly, [LAl(C2H5)Cl] (3) was converted to [LAlCl(μ-OEt)]2 (5) when refluxed in Et2O. 3 gives the monomeric and neutral cyclic (alkyl)(amino) carbene (cAAC) based radical [LAl(C2H5)(cAAC)] (6) on reduction with KC8 in the presence of cAAC. © 2021 The Authors. Zeitschrift für anorganische und allgemeine Chemie published by Wiley-VCH GmbH